Nutritional value and kinetics of the ruminal fermentation of flowers, tree fruits and shrubs in the Cauto Valley, Cuba - Ju?rez, A. S.; Cerrillo, Mar?a A.; La O, Orestes; Herrera, Rafael Segundo; Scull, Idania; Guerero, Maribel; Bernal, H. (Cuban Journal of Agricultural Science, 2013)
The nutritional value and ruminal fermentation kinetics was studied in flower samples (Baryxylum inerme Roxb, Tabebula maestrensis Urb. and Hibicus rosasinensis) and fruit trees and shrubs (Samanea saman Merr, Licania campestre, Prosopis chilensis, Lysiloma bahamensis, Eugenia psiloclados Urb. and Moringa oleifera Lam) of the Cauto Valley in Cuba. The chemical constituents, the gas production at different incubation times, the non-degraded apparent residue, the concentration of volatile fatty acids and the in vitro true digestibility of OM and DM were determined. The DM, OM, ash and EE differed (P < 0.05) between species, while the CP and NDF reached values of up to 26 and 25 %, respectively, without differences. The production of gases derived from the fermentation of the degradable fraction b differed (P < 0.05) in the flowers and pods with seeds. In the flowers, the superior values for this variable were found in H. rosasinensis, while, in the group of pods with seeds were in L. brahamensis. In the flowers, the constant rate of gas production c was higher in T. maestrensis (0.081/h), being superior (0.115 /h) in the pods with seeds E. psiloclado. There were differences (P < 0.05) in the true digestibility of DM and OM in flowers and pods with seeds. The concentration of volatile fatty acids in pods with seeds varied (P < 0.05), while in the flowers, only the acetic acid was different (P < 0.05). The flowers of T. maestrensis and H. rosasinensis, as well as the pods with seeds of S. saman, P. chilensis and E. psiloclados could be alternatives for cattle supplementation. Researches to assess the productive response of the animals through the use of these species and their performance under different management conditions and edaphoclimatic regions are recommended. Key words: in vitro, gas production, chemical composition, digestibility.